Assessing interacting impacts of artisanal and recreational fisheries in a small Marine Protected Area (Portofino, NW Mediterranean Sea). Issue 12 (13th December 2016) - Prato, Giulia; Barrier, Celine; Francour, Patrice; Cappanera, Valentina; Markantonatou, Vasiliki; Guidetti, Paolo; Mangialajo, Luisa; Cattaneo‐Vietti, Riccardo; Gascuel, Didier
Abstract: Marine Protected Areas (MPAs) have spread across the Mediterranean to protect its rich biodiversity and manage human activities for a more sustainable coastal development. Within MPAs, traditional artisanal fishing is competing for space and resources with increasing recreational fishing, likely leading to interacting ecological effects. Such effects are difficult to unravel, given the multispecies character of both fisheries and the complexity of the food webs upon which they both impact. To address these issues, we developed an Ecopath and EcoTroph trophic model for the Portofino MPA case study (NW Mediterranean), in particular to (1) identify keystone species and assess fishing impact on them; (2) analyze the interacting impact of artisanal and recreational fishing on ecosystem biomass and trophic structure; and (3) assess the impact of recreational fishing on artisanal fishing catches. Two high trophic level predator (HTLP) groups coupled important keystone roles with high sensitivity to fishing pressure and should thus be regarded as "sentinels" to be prioritized for the definition of management actions. Recreational fishing had the widest impact on the food web, strongly impacting HTLP. Simulation of different mortality scenarios for each fishery highlighted that the ecosystem is far from its carrying capacity for HTLP. Forbidding recreational fishing allowed a 24% increase in HTLP biomass and benefited artisanal fishing by increased availability of HTLP catches. Artisanal fishing alone could instead be maintained with a moderate impact on the food web. Overall, Ecopath and EcoTroph modeling is a valuable tool to advise MPA management, but it is essential to increase data availability and quality by developing long‐term monitoring programs on key species and on artisanal and recreational fishing.